Vitamin D Deficiency/Insufficiency and Anxiety Among Saudis: Degree and Differences - Al Hariri , Ahmed (European Scientific Journal, ESJ, 2016)
Background: Vitamin D deficiency/insufficiency and anxiety are rapidly growing epidemics among Saudis. Objectives: This study aims to explore the degree and rates of anxiety among Saudis with vitamin D deficiency and insufficiency, to investigate the anxiety means differences between males and females with low vitamin D levels, and to investigate the anxiety means differences between the participants of the same gender in each of two groups, those with vitamin D deficiency and those with insufficiency. Methods: A cross-sectional study was carried out on 228 Saudi participants from two medical centres in Riyadh, Saudi Arabia. A structured questionnaire was used to measure anxiety, and the lab analysts at the two centres reported the participants’ vitamin D levels based on their blood tests. Results: The anxiety mean among Saudis with vitamin D deficiency was higher than among their peers with vitamin D insufficiency. Significant differences in anxiety means existed between males and females with vitamin D insufficiency by a large magnitude, and between males in both groups, with vitamin D deficiency and insufficiency, by a moderate magnitude. Conclusion: Although Saudi females were higher in their anxiety means in both groups, vitamin D deficiency and insufficiency, both anxiety and low vitamin D levels are continuous problems in Saudi Arabia. Hence, more could be done to foster awareness and to combat these issues through consuming vitamin D supplements and increasing food quality.